Assessment and evaluation of attitudes, knowledge, and barriers to evidence-based practice among Fatima college of health sciences educators, UAE - Salih, Suliman; Alkatheeri, Ajnas; Razak, Wuni Abdul; Nordin, Mohd Nazmi; Banu, Shaik Balkhis; Hammoud, Emne; Sachdeva, Monika; Kamil, Noon; Aldawsari, Aisha Namshan; Yadgir, Tanveer; et al. (Edelweiss Applied Science and Technology, 2024)
Evidence-based practices are widely acknowledged as important in improving healthcare quality and achieving excellence in patient care. It is necessary to teach students how to implement evidence-based practice in clinical. Health sciences educators’ awareness of evidence-based practice plays an essential role in implementing this concept in practice which will be reflected in the student’s performance and enhance patient care in the future. This study aimed to assess attitudes, beliefs, knowledge, and behaviour regarding evidence-based practice among allied healthcare educators of Fatima College of Health Science (FCHS). This is a cross-sectional survey study. The survey was distributed among 165 healthcare professional educators in nursing, radiography and medical imaging, physiotherapy, paramedics, psychology, pharmacy, and general requirements departments at the four campuses of the Fatima College of Health Sciences: Al-Dhafra, Abu-Dhabi, Al-Ain, and Ajman. The response rate was 33.3% (n=55). The result showed that the most preferred source of information for educators was electronic research engines 55% (n=30). The data obtained indicated that approximately 95% (n=52) of educators believe that Evidence-Based Practice (EBP) improves patient care, enhances outcomes, and supports sound clinical decision-making. Additionally, 91% of educators agree that the concept of EBP should be incorporated into all college programs. However, the primary barrier to implementing EBP is identified as a lack of time. The study revealed a positive attitude toward EBP among FCHS educators but highlighted the need for more knowledge-sharing opportunities. Time constraints were the main challenge.